Sex differences in risk factors for cardiovascular disease: the PERU MIGRANT study. - Antonio Bernabe-Ortiz; Catherine Pastorius Benziger; Robert H Gilman; Liam Smeeth; J Jaime Miranda (PLoS ONE)
Introduction Although men and women have similar risk factors for cardiovascular disease, many social behaviors in developing countries differ by sex. Rural-to-urban migrants have different cardiovascular risk profiles than rural or urban dwellers. The objective of this study was to evaluate the sex differences with specific cardiovascular risk factors in rural-to-urban migrants. Methods and results We used the rural-to-urban migrant group of the PERU MIGRANT cross-sectional study to investigate the sex differences in specific cardiovascular risk factors: obesity, hypertension, metabolic syndrome, as well as exposures of socioeconomic status, acculturation surrogates and behavioral characteristics. Logistic regression analysis was used to characterize strength of association between sex and our outcomes adjusting for potential confounders. The sample of migrants was 589 (mean age 46.5 years) and 52.4% were female. In the adjusted models, women were more likely to be obese (OR=5.97; 95%CI: 3.21-11) and have metabolic syndrome (OR=2.22; 95%CI: 1.39-3.55) than men, explaining the greatest variability for obesity and metabolic syndrome but not for hypertension. Conclusions Our results suggest that interventions for CVD in Peru should be sex-specific and address the unique health needs of migrant populations living in urban shantytowns since the risk factors for obesity and metabolic syndrome differ between males and females.